Hidden meanings and subtle speech: Off-record politeness strategies in Disney’s Tangled movie - Larissa Kirana Syarief; Uswatun Hasanah; Dirham Abdul Azhim; Lusi Lian Piantari (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2025)
Communication plays an essential role in everyday social interaction, particularly in maintaining harmonious relationships and protecting individuals’ social image or “face.” One way speakers achieve this is through the use of politeness strategies, especially off-record strategies, which allow messages to be conveyed indirectly. This study examines how off-record politeness strategies are used in Disney’s animated movie Tangled through a discourse analysis approach. The analysis focuses on how characters employ indirect speech to manage relationships, reduce conflict, and influence others while preserving social harmony. Using a qualitative method, the study observes and interprets language use in its natural context, emphasizing meaning, identity, and social interaction rather than grammatical structure alone. The findings show that off-record strategies, such as hints, humor, irony, and metaphor, are frequently used by the characters to protect both the speaker’s and the listener’s face. These strategies enable the characters to achieve their communicative goals without causing confrontation. Overall, the study highlights the importance of off-record politeness strategies in fostering respectful and effective communication, not only in fictional narratives but also in real-life social interactions. Understanding these strategies can help individuals communicate more thoughtfully and maintain positive interpersonal relationships.